Special duty a history of the Japanese intelligence community - Samuels, Richard J. (Cornell University Press, 2019)
"Two decades into the 21st century, after more than a century of dangerously uneven performance that contributed to national devastation and often uncomfortable subordination to their powerful U.S. ally, Japanese leaders have begun to reinvent their nation's flawed intelligence community"-- Provided by publisher